Vaccination strategies for cross-protective immunity against African Horse Sickness Virus (AHSV) - Manning, N (2017)
African Horse Sickness (AHS) is a highly lethal arboviral disease of equines. The lack of treatment makes vaccination essential. However, there are nine AHSV serotypes and AHSV immunity is serotype-specific; therefore AHSV vaccines must protect against all serotypes circulating in the field. A commercial polyvalent live-attenuated vaccine has been used for decades. However, bio-safety risks associated with its use, derived from gene segment re-assortment between vaccine and field strains, prompted the development of safer alternatives. These include the use of recombinant Modified Vaccinia Ankara virus (MVA). Previous studies showed that recombinant MVA vaccines expressing the AHSV outer-capsid VP2 protein successfully induced homologous protection and that a polyvalent MVA-VP2 vaccine could be developed (Manning et al., 2017). MVA vaccines expressing full length VP2 or fragments thereof, including a truncated-VP2 lacking the central VP2 immunodominant region, indicated that the structural integrity of VP2 was critical for preservation of neutralising epitopes. Further studies aimed at enhancing MVA-VP2 immunogenicity showed that monovalent MVA-VP2, expressing full-length VP2 from 'immediate-early' vaccinia promoters, could be used in a multivalent vaccination regime inducing homologous protection. To improve the design of polyvalent MVA-VP2 vaccines, a novel strategy based on using bivalent MVA-VP2, expressing two VP2 proteins from different serotypes, was proven successful. Homologous protection conferred by a bivalent MVA-VP2 for AHSV-4 and -9 was comparable to its monovalent counterpart. Previous studies showed MVA-VP2 immunogenicity depends on levels of VP2 protein presented to the immune system at the time of vaccination, since purified MVA-VP2 failed to induce virus neutralising antibodies (VNAb). Further studies described in this thesis, showed the addition of carbopol adjuvant improved immunogenicity of purified MVA-VP2 vaccines. MVA recombinants were produced expressing conserved AHSV capsid proteins, including VP5, VP7 and VP3, and immunogenicity of MVA-VP3 was tested which did not confer any protection against challenge. Various single and dual-expression MVA viruses were generated which will enable generating virus-like-particle AHSV vaccines by MVA expression, which has not been reported previously.